Screening of PAX6 gene in Italian congenital aniridia patients revealed four novel mutations. (2nd July 2016) - Primignani, Paola; Allegrini, Davide; Manfredini, Emanuela; Romitti, Lorenza; Mauri, Lucia; Patrosso, Maria Cristina; Veniani, Emanuela; Franzoni, Alessandra; Del Longo, Alessandra; Gesu, Giovanni Pietro; Piozzi, Elena; Damante, Giuseppe; et al.
ABSTRACT: Purpose : To uncover underlying mutations in a cohort of Italian patients with aniridia, a rare congenital panocular condition with an incidence ranging from 1:64, 000 to 1:100, 000. The disease may be found isolated or in association with other syndromes characterized by partial or complete absence of the iris and iris hypoplasia. Methods: We analyzed the PAX6 gene in 11 patients with aniridia fulfilling the following inclusion criteria: partial or complete absence of the iris and age < 18 years at the time of diagnosis. DNA sequence analysis was integrated with Multiple Ligation Probe Assay (MLPA) analysis. Results: We identified seven PAX6 mutations, including four novel ones. The majority of mutations lie in the DNA-binding domain and all produce a truncated protein. All tested patients did not have WT1 gene deletions thus excluding the WAGR syndrome. We present the clinical findings in the four cases harboring novel mutations. We were unable to identify mutations in four cases with complete aniridia thus indicating that other gene/s could be involved in the disease. Conclusions: It is important to establish the molecular diagnosis early to avoid repeated and long-term screening for Wilms tumor. Our work further emphasizes that a wide range of ocular phenotypes are associated with loss of function PAX6 mutations. In addition to the possibility of stochastic variations, other genetic variations could play a role as modifier genes, thus giving rise to the observed different ocular phenotypes.